Effects of artificial diets with different carotene content on the organoleptic characteristics of the gonads and reproductive condition of Loxechinus albus (Echinodermata: Echinoidea) - Fraysse, Cintia; Malanga, Gabriela; Pérez, Analía F. (Revista de Biología Tropical, 2017)
The organoleptic characteristics of sea urchins gonads (size and color, among others) can be improved by artificial diets. Loxechinus albus is considered one of the most economically significant resources from the littoral-benthic systems in the South Pacific Ocean from Peru to Chile. The objective was to determine artificial diets effects on the organoleptic traits of gonads, reproductive condition, body growth and survival of Loxechinus albus. Two types of diets were administrated (low carotene content diet (LC): balanced food with 0.02% β-carotene and high carotene content diet (HC): balanced food with 0.045% β-carotene) for 16 weeks. As a measurement of growth rate, test diameter of sea urchins fed with artificial diets was measured at the beginning and at the end of the experiment. At both times, size (GI) and color (CI) of the gonads were recorded in ten individuals from each treatment and ten from the natural population (NP). Energy density (ED), energy content (EC) and total carotenes (TCC) were determined by calorimetry and spectrophotometry, respectively. Histological sections were examined microscopically and the sex was identified. Each female was assigned to a gametogenic stage (reproductive condition) and determined: number and diameter of the oocytes, gonadal area occupied by oocytes, and relative frequencies of reproductive stages. At the end of the experiment in relation to the NP, it was possible to achieve higher GI values for both artificial diets. The NP showed higher gonadal area occupied by oocytes and larger oocyte diameter at 16 weeks (P<0.01). In addition, individuals fed with both artificial diets, presented “growth” and “advanced growth” gonad stages (both times), while the NP individuals, presented stages of “prematurity”, “maturity” and “partial spawning” at week 16. The data shows the highest CI value for the HC diet at eight weeks (P<0.01). Moreover, TCC values for the NP were significantly higher at week 16 (P<0.01). Loxechinus albus is an appropriate species to be kept in captivity, as their mortality is very low, facilitating the achievement of long-term experiences of gonadal improvement. According to our data the optimal time to improve the organoleptic characteristics is eight weeks with a high carotene artificial diet, since optimal gonad coloration was reached, and GI values did not differ significantly from the ones achieved at the end of the experiment for both diets, or the ones shown in the NP. This is translated into a lower cost by a reduced cultivation time. Rev. Biol. Trop. 65(Suppl. 1): S207-S220. Epub 2017 November 01.